Asssessment and rehabilitation of chronic low back pain in baseball: part ii - Wasser, J. G.; Zaremski, J. L.; Herman, D. C.; Vincent, H. K. (Research in Sports Medicine, 2017)
Repetitive throwing and hitting motions in baseball place mechanical stresses to the lumbar spine which may cause low back pain (LBP). Pain may be due to vertebral stress reactions or insufficiency fractures, intervertebral disc degeneration or intervertebral disc herniation. Untreated chronic conditions have high potential to lead to a more significant injury such as spondylolysis. Chronic LBP increases the risk for missed playing time, early career termination and lower quality of life after retirement. Proper clinical assessment and prevention/rehabilitation of LBP in this population is thus important for performance, play time and overall long-term quality of life. This narrative review synopsizes the available evidence for assessment and rehabilitation of baseball players with LBP, including the structured rehabilitative techniques and programmes which should be administered to affected players. The state of the evidence suggests that there are deficits in identifying the optimal prevention and rehabilitation prescription components for the variety of LBP-inducing injuries in this athletic population.